2020
DOI: 10.1007/s42729-020-00183-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Concentration in Leafy Vegetables from the Central Zone of Chile: Sources and Environmental Factors

Abstract: Leafy vegetables constitute an excellent source of fiber, vitamins, minerals, and phytochemicals, producing many benefits to human health. However, nitrate (NO 3 -N) accumulation constitutes a risk factor for environment and human health. The present study was focused on the evaluation of concentrations and sources of NO 3 -N in lettuce and spinach under different production systems, located in the Metropolitan region (Chile). Nitrate concentration was determined in vegetable tissue, soil, water, and organic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A diagram of the row spacing and plant spacing measurements is shown in Figure 1d. The measured N content of Lactuca sativa seed was 2.436% [24] and the ideal Lactuca sativa dry matter N content was 4.831% [25], with a biomass of 199.8 g for a 1 m 2 planting area [26]. The amount of fertilizer required for this trial was 21.61 g per square meter of seed sown, which was converted to a combination of 40% compound fertilizer and 60% urea at 49.7 g. The specific fertilizer application rates are shown in Table 2.…”
Section: Design Of Experimentsmentioning
confidence: 95%
“…A diagram of the row spacing and plant spacing measurements is shown in Figure 1d. The measured N content of Lactuca sativa seed was 2.436% [24] and the ideal Lactuca sativa dry matter N content was 4.831% [25], with a biomass of 199.8 g for a 1 m 2 planting area [26]. The amount of fertilizer required for this trial was 21.61 g per square meter of seed sown, which was converted to a combination of 40% compound fertilizer and 60% urea at 49.7 g. The specific fertilizer application rates are shown in Table 2.…”
Section: Design Of Experimentsmentioning
confidence: 95%
“…Nitrate accumulation in vegetables could be immediately linked to N fertilization practices, excess nitrogen applied resulted in increased NO3 accumulation (Ortega-Blu et al, 2020). Various studies reported a significant positive correlation between NO3 content in leafy vegetables and the dose of nitrogen supply (Fu et al, 2017;Urlić et al, 2017).…”
Section: Introductionmentioning
confidence: 98%